2017
DOI: 10.14444/4032
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Different Methods of Fixation in the Management of Thoracolumbar Fractures

Abstract: Introduction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Similarly, Sapakas, et al found a statistical significant difference when comparing SSPSF to LSPSF in terms of follow up Cobb's angle with favourable measures found in LSPSF group [16]. Panteliadis, et al compared three modalities for posterior spinal fixation in thoracolumbar burst fractures (1 level above and 1 level below, 2 above and 1 below, and 2 above and 2 below the fracture) and found that better correction maintained in the 2 above and 2 below group compared to the others but with no statistically significant difference [20].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sapakas, et al found a statistical significant difference when comparing SSPSF to LSPSF in terms of follow up Cobb's angle with favourable measures found in LSPSF group [16]. Panteliadis, et al compared three modalities for posterior spinal fixation in thoracolumbar burst fractures (1 level above and 1 level below, 2 above and 1 below, and 2 above and 2 below the fracture) and found that better correction maintained in the 2 above and 2 below group compared to the others but with no statistically significant difference [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examining TL trauma topics have also begun to routinely use AOSpine TLICS for the classification of the study of the subject's injuries. [42][43][44] Overall, AOSpine TLICS/TL AOSIS represents the culmination of an international effort to combine the AO/ Magerl system and TLICS into a universally accepted TL trauma classification system with an emphasis on fracture morphology, neurological status, and a score-based treatment algorithm. While intra and interrater reliability remains a potential concern, the international spine community has demonstrated an early willingness to embrace AOSpine TLICS/TL AOSIS during the first decade since its development, and future work will certainly continue to build upon this foundation.…”
Section: Aospine Thoracolumbar Spine Injury Classification Systemmentioning
confidence: 99%
“…Nagi and Sakr41 also demonstrated in 2022 that the current management of TL trauma adheres slightly more closely to TL AOSIS (88.6%) than TLICS (85.7%). Recent studies examining TL trauma topics have also begun to routinely use AOSpine TLICS for the classification of the study of the subject’s injuries 42–44…”
Section: Historic Overviewmentioning
confidence: 99%
“…При повреждении без неврологических симптомов прибегают к довольно новой методике: транскутанной транспедикулярной фиксации полиаксиальными винтами (рис. 1), которая выполняется из нескольких разрезов до 1,5 см (их число зависит от числа устанавливаемых транспедикулярных винтов) [5]. Предварительно перед операцией возможно проводить закрытую репозицию, реклинацию, основанную на механизме лигаментотаксиса (устранение смещения отломков и деформации позвоночного канала путем открытой репозиции и манипуляции с помощью транспедикулярного фиксатора).…”
Section: малоинвазивные методы хирургического леченияunclassified
“…Реконструкция передней колонны позвоночника ранее проводилась через довольно травматичные и технически сложные ретроперитонеальный, трансторакальный, транслюмбальный доступы, в том числе и с необходимостью резекции ребер или пересечения диафрагмы. В настоящее время технологии позволяют выполнять данный этап вмешательства, используя малоинвазивные методы: торакоскопические и лапароскопические, позволяющие проводить переднюю декомпрессию, замещение поврежденных тел позвонков и межпозвонковых дисков опорными реконструктивными устройствами [5]. Данная методика является технически сложной и требует определенного уровня подготовки хирурга, но значительно снижает травматичность вмешательства, интенсивность послеоперационного болевого синдрома, дает возможность начать максимально раннюю активизацию пациента (рис.…”
Section: малоинвазивные методы хирургического леченияunclassified